The physicochemical features of eggshell, thick albumen, amniotic fluid, and yolk during chicken embryogenesis - Jakub Biesek (Poultry Science, 2023)
ABSTRACT: The study aimed to analyze the hatching egg and physiochemical features of eggshells, thick albumen, amniotic fluid, and yolk during the incubation of Ross 308 chicken eggs. Eggs (n = 755) were incubated for 21 d. Quality analysis of fresh eggs was performed. Eggshells, albumen, and yolk were collected from fresh eggs and incubation d 1, 7, and 14. Eggshell thickness and strength, pH, vitelline membrane strength, fatty acid (FA) in the yolk, pH, viscosity, lysozyme activity, and crude protein content in thick albumen and amniotic fluid were analyzed. Hatching parameters were calculated. Egg weight loss was constant (8.04% overall). Lower egg surface temperature was found on d 7 compared to d 4, 14, and 18. A lower thickness of posthatch eggshells was found. The strength of the vitelline membrane significantly decreased within 24 h (by over 58%). During incubation, there was a decrease in thick albumen/amniotic fluid pH; an opposite trend was found in yolk pH. The vitelline membrane strength was negatively correlated with the albumen pH. Lysozyme activity was higher in fresh thick albumen and up to 2 wk of incubation. On d 7, the lowest activity was found in the amniotic fluid. On d 14, lysozyme activity increased in amniotic fluid. The higher viscosity of the thick albumen was demonstrated on d 7 and 14 of incubation. The lowest viscosity in amniotic fluid was found on the same days. Crude protein content was higher in thick albumen (d 7 and 14) and lowest in amniotic fluid on d 7. The FA content changed between d 0 and 14. The results indicate different use of FA, where PUFA decreased. Eggshell is used in the last week of incubation. The thick albumen is reduced, while the biological value of amniotic fluid is increasing. Lysozyme activity, viscosity, and crude protein content may be interdependent. It may indicate the flow of substances and the transfer of functions from the thick albumen to the amniotic fluid during chicken embryogenesis.